EFFECTIVE VOCABULARY TEACHING IN THE LEARNING PROCESS - Berdikulova Munira Azizovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. Vocabulary is one of the most important language-learning skills. Without vocabulary, we cannot improve our language learning skills. It is highlighted that beneficial ways and methods are cruel to use in vocabulary teaching. In this article, effective ways of vocabulary teaching are depicted in the teaching and learning process.